2005
DOI: 10.1111/j.0022-202x.2004.23593.x
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene Interferes with Ultraviolet Light A-Induced Gene Expression by Multiple Pathways

Abstract: Ultraviolet light A (UVA) exposure is thought to cause skin aging mainly by singlet oxygen ((1)O(2))-dependent pathways. Using microarrays, we assessed whether pre-treatment with the (1)O(2) quencher beta-carotene (betaC; 1.5 microM) prevents UVA-induced gene regulation in HaCaT human keratinocytes. Downregulation of growth factor signaling, moderate induction of proinflammatory genes, upregulation of immediate early genes including apoptotic regulators and suppression of cell cycle genes were hallmarks of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 24 publications
0
57
0
Order By: Relevance
“…It has been shown that b-carotene can modulate UV-A-induced gene expression in human keratinocytes [221]. Carotenoids have also been assessed in relation with their antioxidant properties [47] that can play a key role in reducing the incidence of several UVR-mediated diseases [6].…”
Section: Photoprotective Compounds: Commercial Applicationsmentioning
confidence: 99%
“…It has been shown that b-carotene can modulate UV-A-induced gene expression in human keratinocytes [221]. Carotenoids have also been assessed in relation with their antioxidant properties [47] that can play a key role in reducing the incidence of several UVR-mediated diseases [6].…”
Section: Photoprotective Compounds: Commercial Applicationsmentioning
confidence: 99%
“…This, in turn, leads to degradation, e.g. of the extracellular matrix proteins, by inducing matrix metalloproteases [30]. On the contrary, antioxidants such as β-carotene significantly reduce stress and degradation of the extracellular matrix, in addition to promoting the differentiation of keratinocytes [31], which might explain the improved skin parameters that we observed.…”
Section: Discussionmentioning
confidence: 98%
“…There are quite a few natural compounds, which can prevent from UV damage: α-tocopherol which prevents UVA-and UVB-induced glutathione loss and reduce induction of DNA damage by UVB [19,20]. β-Carotene which inhibits free radicals and cause higher resistance to immunosuppression after exposure to UV light [21]; lycopene which absorb light in the UV range and increase the toughness of the skin [22,23]. Lutein which prevent extracellular matrix breakdown and prevents skin from UV damage [24]; flavonoids such as isorhamnetin, quercetin, kaempferol which significantly decreased erythema developed after UVB irradiation [25], and green tea polyphenols which reduce UV-induced p53 expression and keratinocytes apoptosis and protect from DNA damage [26], and others.…”
Section: Short Communicationmentioning
confidence: 99%